HARMONISASI REGULASI DAN EFEKTIVITAS KELEMBAGAAN SAFEGUARD DI INDONESIA - Abdurrahman Alfaqiih (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The implementation of WTO agreement is not easy in accordance with the estabilished regulations, so deviations in the process of trade liberalization that press domestic indrusties will likely to take place. Therefore, it is necessary to have safety actions to actualize mutual benefits in international trade. There are many cases of safety actions conducted by many countries such as Argentine that implements safety actions to its footwear industries without adapting to WTO regulations which causes the country’s losses. The paper examines the consistency of safeguard regulations in Indonesia with safeguard regulations of WTO and its implementation reviewed from the law effectiveness. The result of the study shows that the safeguard regulations in Indonesia is in accordance with the safeguard regulations of WTO in the normative level, but in the implementation the policy is not done effectively.